Rigidity‐Patterned Polyelectrolyte Films to Control Myoblast Cell Adhesion and Spatial Organization. (7th February 2013) - Monge, Claire; Saha, Naresh; Boudou, Thomas; Pózos‐Vásquez, Cuauhtemoc; Dulong, Virginie; Glinel, Karine; Picart, Catherine
Abstract In vivo, cells are sensitive to the stiffness of their microenvironment and to the spatial organization of the stiffness. In vitro studies of this phenomenon can help to better understand the mechanisms of the cell response to spatial variations of the matrix stiffness. Here, polelyelectrolyte multilayer films made of poly(L‐lysine) and a photoreactive hyaluronan derivative are designed. These films can be photo‐crosslinked through a photomask to create spatial patterns of rigidity. Quartz substrates incorporating a chromium mask are prepared to expose selectively the film to UV light (in a physiological buffer), without any direct contact between the photomask and the soft film. It is shown that these micropatterns are chemically homogeneous and flat, without any preferential adsorption of adhesive proteins. Three groups of pattern geometries differing by their shape (circles or lines), size (from 2 to 100 μm), or interspacing distance between the motifs are used to study the adhesion and spatial organization of myoblast cells. The results pave the way for the study of the different steps of myoblast fusion in response to matrix rigidity in well‐defined geometrical conditions.